Konstitusionalisasi Tata Kelola Digital: Implementasi Undang-Undang Perlindungan Data Pribadi dalam Perspektif Hukum Teknologi Informasi - Firmantoro, Kiki (Neolectura, 2025)
This study examines the constitutionalization of digital governance through the implementation of Law No. 27 of 2022 on Personal Data Protection (UU PDP) within three corporate contexts in Indonesia. Using a normative-empirical approach grounded in information technology law, the research analyzes governance responses in a national manufacturing company and two publicly reported cyber incidents involving major financial and e-commerce institutions affected by phishing and data breaches. These cases demonstrate structural weaknesses in digital risk management that resulted in operational disruption, financial loss, and reputational harm. The findings indicate that compliance with UU PDP requires more than procedural adjustment; it necessitates embedding constitutional privacy principles into corporate digital architecture. Effective protection depends on risk-based governance, privacy-by-design integration, and institutional accountability to transform regulatory compliance into sustainable constitutional digital governance